(untitled) (Journal of Comparative Social Work, 2010)
Over the last two decades or so, major Western societies have remoulded the institutional set-up by which they are deailing with social risks related to frailty during old age. While the 20th century had brought a transnational tendency towards the establishment of elderly care ‘going public’, the proliferation of more market-based services brings confusion into the societal norm-set underlying the aforementioned tendency. Marketisation has placed the emphasis on economic values engrained in liberal worldviews, leading into a new welfare culture that devaluates universalism and reemphasises the sovereignty of the individual. However, the new cult of the individual produces contradictory signals. Drawing on an encompassing study on the ‘culture of welfare markets’ in elderly care provision, covering two (post-)liberal and two (post-corporatist) welfare regimes (Canada, Britain; France, Germany), the paper looks at these fuzzy developments in order to assess the cultural embeddedness of what can be referred to as the mixed economy of elderly care. The analysis, charting major patterns of both institutional change and public communication around it, elucidates that we currently are facing a permanent struggle between liberal values and (renewed) elements of the ‘going-public-agenda’ proliferating over the 1970s and 1980s, that is, a hybrid and ‘nervous’ cultural configuration in which senior social citizenship remains an issue, albeit on precarious foundations.